2022
DOI: 10.3390/healthcare10112178
|View full text |Cite
|
Sign up to set email alerts
|

Wrist Rigidity Evaluation in Parkinson’s Disease: A Scoping Review

Abstract: (1) Background: One of the main cardinal signs of Parkinson’s disease (PD) is rigidity, whose assessment is important for monitoring the patient’s recovery. The wrist is one of the joints most affected by this symptom, which has a great impact on activities of daily living and consequently on quality of life. The assessment of rigidity is traditionally made by clinical scales, which have limitations due to their subjectivity and low intra- and inter-examiner reliability. (2) Objectives: To compile the main met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Table 2 shows that there is no study on rigidity monitoring with the wrist-based sensor in a daily environment. A recent scoping review of wrist rigidity evaluation reported that some force and inertial sensors have been used to quantitatively assess the rigidity of wrists in PD ( Alves et al, 2022 ). However, it is challenging to standardize the measurement of rigidity with accessible wearables.…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 shows that there is no study on rigidity monitoring with the wrist-based sensor in a daily environment. A recent scoping review of wrist rigidity evaluation reported that some force and inertial sensors have been used to quantitatively assess the rigidity of wrists in PD ( Alves et al, 2022 ). However, it is challenging to standardize the measurement of rigidity with accessible wearables.…”
Section: Discussionmentioning
confidence: 99%
“…It not only affects the limbs but also effect on facial muscles, neck and trunk [8]. PD Patients experienced cogwheel rigidity (a jerky resistance to movement) and lead-pipe rigidity (a constant resistance throughout the movement) [9]. Rigidity in PD makes it hard to initiate a movement, do ne motor tasks, balance and co-ordination and maintain a relaxed posture.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical rigidity the relaxation of the antagonist fails, reducing the loss of the range of motion. The supinator-pronation of the extended wrist has clinical value in defining rigidity [3]. Unfortunately, this "low tech" observation rarely finds utility beyond the movement specialist neurologist.…”
Section: Introductionmentioning
confidence: 99%
“…Dystonia may show involuntary muscle contractions in the wrist and hand, leading to abnormal movements or postures. Common symptoms include twisting of the wrist, flexion or extension of the fingers, and difficulty controlling wrist movements [3]. During the disability determination, the loss of wrist rotation while the elbow is bent defines a graded "whole person impairment" as specifically outlined by Cocchiarella and Anderson [12].…”
Section: Introductionmentioning
confidence: 99%